Mineral surface area of sinking particles in the deep ocean interior: Preliminary implications - Minkyoung Kim; Thomas M. Blattmann; Baozhi Lin; Sun‐A Lee; Daniel B. Montluçon; Timothy I. Eglinton (Limnology and Oceanography Letters)
Abstract Measurement of the mineral surface area (MSA) of sedimentary particles is a traditional approach for studying the transport and protection of organic carbon (OC) in marine systems. We investigated the application of MSA on the biological carbon pump in the deep ocean interior in the Ulleung Basin (UB), East/Japan Sea. This is the second study of sinking particle MSA, and the first in an ocean with no major riverine (terrestrial) input. We measured seasonal and vertical variations in the MSA of sinking particles and adjacent surface sediments in the UB. Mineral surface area values exhibit seasonal variations associated with particle composition, with a negative correlation with OC content and a strong positive correlation with the content of lithogenic material and the radiocarbon values of sinking OC. Our results indicate that the MSA of sinking particles may provide clues to the processes of particle resuspension and decomposition.